Peningkatan Kemampuan Mahasiswa Pendidikan Guru Dalam Menyusun Perangkat Pembelajaran Melalui Refleksi Diri Pada Mata Kuliah Pendidikan IPA Sekolah Dasar - Yulinda Dwi Saputri*; Banu Setyo Adi; Woro Sri Hastuti; Rahayu Condro Murti (Universitas Syiah Kuala, 2023)
The ability of elementary school teacher education students at Yogyakarta State University in compiling learning tools is still low. It is proven from the results of the learning tools that are not in accordance with the writing procedures and characteristics of elementary school students, the content is not appropriate, and the components are not complete. The solution that can be done is to do self-reflection on the learning tools they have arranged. This study aims to improve the ability of teacher students in compiling learning through self-reflection in the Elementary School Science Education course. This research uses the classroom action research method. The subjects of this study were 4th-semester Elementary School Teacher Education students in class C. The data were processed and analyzed descriptively, quantitatively, and qualitatively. The results showed that the student's ability in preparing science learning tools had an average initial score of 75.43 and increased to 95 after the first cycle was carried out by self-reflection through the instrument. The student's ability increased again after the second cycle was carried out by adding treatment in the form of giving instruments and conducting peer discussions and expert experts. This increase obtained an average score of 98. It was concluded that self-reflection can help students analyze shortcomings and find solutions and make improvements so that they can develop good science learning tools as a provision to become professional teachers